Nutritional recommendations and management practices adopted by feedlot cattle nutritionists: The 2016 Brazilian survey - Pinto, Ana C. J. [UNESP]; Millen, Danilo D. [UNESP] (Canadian Science Publishing, 2019)
The feedlot industry in Brazil is still evolving, and some nutritional management recommendations adopted by nutritionists changes from year to year. The main objective of this survey was to provide a snapshot of current nutritional management practices adopted in Brazilian feedlots. The 33 nutritionists surveyed were responsible for approximately 4 228 254 animals. Corn remained as the primary source of grain used in feedlot diets by the participants, whereas fine grinding was the primary grain processing method. Corn silage was the primary roughage source indicated by nutritionists, and for the first time, physically effective neutral detergent fiber was the preferred fiber analysis method. The average dietary fat recommended was 50 g kg−1 of dry matter, which is about 10% higher than values reported in previous surveys. The use of truck-mounted mixers increased, which may have increased the percentage of feedlots using programmed feed delivery per pen, allowing the increase of energy content of finishing diets. Feedlots did not increase their capacity and nutritionists reported an improvement in feeding management. Results reported in the current study provide a baseline that can be used to improve practices and aid in the development of feedlot industry in Brazil and similar tropical climates.
Keywords: Cattle; Energy; Feedlot; Nutritionists; Survey